If it's not what You are looking for type in the equation solver your own equation and let us solve it.
15(9x-1)-14=133x+15
We move all terms to the left:
15(9x-1)-14-(133x+15)=0
We multiply parentheses
135x-(133x+15)-15-14=0
We get rid of parentheses
135x-133x-15-15-14=0
We add all the numbers together, and all the variables
2x-44=0
We move all terms containing x to the left, all other terms to the right
2x=44
x=44/2
x=22
| 7x-(2x-10)=25 | | 75=5w+13 | | 4/3=4n | | 2x*(x-2)=7x^2-7x | | 15x-15=7×-13 | | 2x+4+60=90 | | 13=7+3r | | x-1/2=-1/2 | | -2x+12=3x-103 | | x+1.5−0.5x=4.5x+1.5-0.5x=4.5 | | 2+2s=14 | | 54=4y-16 | | 4(x^2+19x+70)=544 | | -18x^2+19x-5=0 | | n/2=3/5 | | =52−4y16 | | 9x+2=7x-24 | | 13=9r+8 | | 2x-1/3x=0 | | -9x^2-9x+28=0 | | -3d+21=6 | | 2(2x-2)=9x | | 12(x+7)=60 | | -5x(3x+4)+2=0 | | (x-3)/4=0 | | 12v+10v14=80 | | -19+x=-20 | | 2+x^-10=2^5 | | 5–2j=1 | | 7x+3(4x-1)=14 | | 2(5+3)=6x-3 | | (2x+3)(5-3x)=0 |